2004
DOI: 10.1007/s10545-005-0479-x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cataract, muscular hypotonia, developmental delay and sensorineural hearing loss associated with a defect in copper metabolism

Abstract: Deficiencies of different proteins involved in copper metabolism have been reported to cause human diseases. Well-known syndromes, for example, are Menkes and Wilson diseases. Here we report a patient presenting with congenital cataract, severe muscular hypotonia, developmental delay, sensorineural hearing loss and cytochrome-c oxidase deficiency with repeatedly low copper and ceruloplasmin levels. These findings were suggestive of a copper metabolism disorder. In support of this, the patient's fibroblasts sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Horvath et al, in 2005, were the first to report this phenotype where they also identified Cytochrome C Oxidase (COX) deficiency in tissue in addition. Though the patient succumbed to the illness, they observed complete reversal of COX deficiency with copper histidinate supplementation (Horváth et al 2005).But a follow up study with four additional cases did not report COX deficiency in any of the patients (Huppke et al 2012). In our patient too, histopathology did not reveal any COX deficiency but showed a relatively low functioning of complex IV on spectrophotometric analysis.…”
Section: Discussionmentioning
confidence: 96%
“…Horvath et al, in 2005, were the first to report this phenotype where they also identified Cytochrome C Oxidase (COX) deficiency in tissue in addition. Though the patient succumbed to the illness, they observed complete reversal of COX deficiency with copper histidinate supplementation (Horváth et al 2005).But a follow up study with four additional cases did not report COX deficiency in any of the patients (Huppke et al 2012). In our patient too, histopathology did not reveal any COX deficiency but showed a relatively low functioning of complex IV on spectrophotometric analysis.…”
Section: Discussionmentioning
confidence: 96%
“…The integrity of this signaling pathway is compromised by mutations in SCO1 and SCO2 (28,45,46). SCO1 and SCO2 patients present with clinically heterogeneous forms of fatal disease that affect liver, heart, or brain function (47)(48)(49)(50)(51)(52)(53)(54). Affected tissues in SCO patients are both COX-and copper-deficient, and both deficiencies appear to be key components of the underlying tissue specificity of disease (46,55).…”
Section: Discussionmentioning
confidence: 99%
“…Urine copper was normal. Horváth et al had previously reported one of those patients, whose muscle biopsies revealed a dilated sarcoplasmic reticulum as the most conspicuous finding [ 128 ]. Huppke-Brendel syndrome is caused by mutations in the SLC33A1 gene, encoding for a transporter (AT-1) that translocates acetyl-CoA into the ER lumen [ 127 ].…”
Section: Copper Homeostasismentioning
confidence: 99%